2014
DOI: 10.1111/cob.12078
|View full text |Cite
|
Sign up to set email alerts
|

The population distribution of the sagittal abdominal diameter (SAD) and SAD/height ratio among Finnish adults

Abstract: Summary Sagittal abdominal diameter (SAD; ‘abdominal height’ measured in supine position) may improve upon conventional anthropometry for predicting incident cardiometabolic diseases. However, the SAD is used infrequently by practitioners and epidemiologists. A representative survey of Finnish adults in 2000–2001 collected body measurements including SAD (by sliding-beam calliper) using standardized protocols. Sampled non-pregnant adults (ages 30+ years; 79% participation) provided 6123 SAD measurements from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…This association has laid the foundation for further research to investigate the capability of various anthropometric measurements (SAD, waist circumference, and BMI) to distinguish individuals with abnormal glucose metabolism [7]. Some earlier investigations have shown that SAD, which can index abdominal fat specifically, may be a more effective predictor than waist circumference or BMI for predicting glucose intolerance and other metabolic disturbances [10, 40–42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association has laid the foundation for further research to investigate the capability of various anthropometric measurements (SAD, waist circumference, and BMI) to distinguish individuals with abnormal glucose metabolism [7]. Some earlier investigations have shown that SAD, which can index abdominal fat specifically, may be a more effective predictor than waist circumference or BMI for predicting glucose intolerance and other metabolic disturbances [10, 40–42]. …”
Section: Discussionmentioning
confidence: 99%
“…The sagittal abdominal diameter (SAD) measurement, also referred to as “abdominal height,” has been introduced as a noninvasive method to index visceral fat [10]. SAD is measured with a subject laying in a supine position so that loose subcutaneous fat falls to the sides, and the harder, more rigid visceral fat stays in place to be measured via a caliper [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing SAD protocols suggest, however, that the NHANES protocol for SAD may be the most appropriate for identifying health risks [46,47]. A very similar protocol for SAD measurement was used successfully in a nationwide survey of over 6000 Finnish adults in 2000–2001 [48]. So long as it is possible for patients or survey participants to lie supine, the convenience and reliability of SAD measured by this standardized protocol may be no less than those of the waist circumferences or weights that are commonly obtained in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the standard anthropometric data did not accurately account for changes in body composition and fat distribution in the elderly, as aging is associated with an increase in fat mass and decrease in height, lean tissue, and muscle mass (28,29). As such, Kahn et al (30) reported a tendency to larger SAD with increasing age. Therefore, this should be considered when generalizing threshold values and cardio-metabolic increased risk from young to older adults.…”
Section: Discussionmentioning
confidence: 94%